Pendapatan nasional: Pendekatan dan konsep perhitungan pendapatan nasional - Silviasari, Nelli; Usidan, Nizar Amud; Muzaki, Miftahul (Maliki Interdisciplinary Journal, 2024)
National income is a measuring tool used to determine the level of the economy in a country within a certain period, which is usually done in one year. The calculation of national income is carried out with the aim of seeing a picture of the level of welfare and prosperity of the people of a country in a certain time period. In calculating a country’s income, there are several approaches, namely, the production approach, the income approach, and the expenditure approach. The results of calculating national income are then divided by the population, and the per capita income of a country is found. The research method used was a literature review, 9 articles were found that were relevant for review and analysis of national income. With data sources obtained through the Google Shcolar website, the Publish or Perish website, and other websites. This data is in the form of journals, articles, documents and data.